2021
DOI: 10.1177/09603271211017609
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and glycolysis independently attenuate silibinin-induced apoptosis in human hepatocarcinoma HepG2 and Hep3B cells

Abstract: Purpose: The mechanism of cytotoxicity of silibinin on two human hepatocellular carcinoma (HCC) cell lines, HepG2 (p53 wild-type) and Hep3B cells (p53 null), is examined in relation with the induction of autophagy and phosphorylation of AMP-activated protein kinase (p-AMPK). Materials and Methods: Levels of apoptosis in relation to the levels of autophagy and those of glycolysis-related proteins, glucose transporter 1/4 (Glut1/4) and hexokinase-II (HK2), in HepG2 and Hep3B cells were examined. Results: Silibin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Another limitation of the studies is that some of them did not investigate the interaction between autophagy and apoptosis in HCC. According to studies, autophagy and apoptosis show interactions in normal and cancerous cells and even in different diseases, and autophagy can sometimes inhibit apoptosis [97][98][99]. However, this role has been ignored in some studies on HCC.…”
Section: Autophagy and Apoptosis Interactionmentioning
confidence: 99%
“…Another limitation of the studies is that some of them did not investigate the interaction between autophagy and apoptosis in HCC. According to studies, autophagy and apoptosis show interactions in normal and cancerous cells and even in different diseases, and autophagy can sometimes inhibit apoptosis [97][98][99]. However, this role has been ignored in some studies on HCC.…”
Section: Autophagy and Apoptosis Interactionmentioning
confidence: 99%
“…Similarly, the long non-coding RNAs (lncRNAs)-hsa-miR-4443-AKT1 pathway responds positively to baicalein treatment[ 35 ]. Studies have further revealed that silibinin induces autophagy through the adenosine monophosphate (AMP)-activated protein kinase (AMPK) pathway and induces apoptosis by up-regulated p21/cyclin-dependent kinases (CDK) 4 and p27/CDK4 complexes, and down-regulated Rb-phosphorylation and E2F1/DP1 complex[ 36 , 37 ]. Lee and Kwon[ 38 ] demonstrated that luteolin causes ER stress in p53-wild type HepG2 cells and Hep3B cells[ 38 ].…”
Section: Augmented Local Controlmentioning
confidence: 99%
“…It was revealed that increased aerobic glycolysis in nasopharyngeal carcinoma cells via the IRF2/CENP-N/AKT axis promoted malignant biological behavior while inhibiting apoptosis ( Qi et al, 2021 ). In hepatocellular carcinoma (HCC), aerobic glycolysis was also found to inhibit Silibinin-triggered apoptosis in human HCC HepG2 and Hep3B cells ( Yang et al, 2021 ). In addition to the glycolysis-mediated suppression of tumor cell apoptosis, its metabolite lactate accumulates in the TME, leading to acidification of the extracellular pH and immunosuppression, which, in turn, affect the TME ( de la Cruz-López et al, 2019 ).…”
Section: The Significance and Related Mechanism Of Glycolysis In Tumo...mentioning
confidence: 99%